2021
DOI: 10.30773/pi.2021.0295
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Dementia Knowledge and Dementia Worry in the South Korean Elderly Population

Abstract: Objective South Korea is one of the countries with a very fast aging rate, and the prevalence of dementia is rapidly increasing. However, there are relatively few studies pertaining to sociodemographic and physical health-related factors associated with dementia knowledge and dementia worry.Methods This was a cross-sectional survey of a community in Seocho-gu, Seoul, Republic of Korea. Overall, 1,869 adults aged 60 years participated. Participants completed an online interview or face-to-face interview. Survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
4
4
0
Order By: Relevance
“…The reason for this positive association might be that medical staff with high levels of monkeypox common knowledge were more aware of the severity of monkeypox global outbreak. The same phenomenon has been found in studies of other diseases [28] , [29] . A recent cross-sectional study of 1,546 participants found that more than 60% of participants were more worried about COVID-19 than monkeypox [12] , similar to our findings (69.3%).…”
Section: Discussionsupporting
confidence: 86%
“…The reason for this positive association might be that medical staff with high levels of monkeypox common knowledge were more aware of the severity of monkeypox global outbreak. The same phenomenon has been found in studies of other diseases [28] , [29] . A recent cross-sectional study of 1,546 participants found that more than 60% of participants were more worried about COVID-19 than monkeypox [12] , similar to our findings (69.3%).…”
Section: Discussionsupporting
confidence: 86%
“…It is important to note a positive association between a high level of knowledge and worry in this study. This phenomenon was also reported in other diseases (42)(43)(44). The reason for this positive association may be that people with a high knowledge level are more likely to understand the susceptibility and severity associated with mpox and the global outbreak, especially for those affected by the COVID-19 pandemic substantially.…”
Section: Education Levelsupporting
confidence: 57%
“…Dementia worry was found to be relatively low in both countries, as the average score was 1.78 and 1.67 for Israel and Australia, respectively, out of a 1–5 range, although it was significantly higher in Israel than in Australia, supporting our first hypothesis. Moreover, as hypothesized and similar to previous studies [ 5 , 6 , 7 , 34 , 35 , 36 ], positive and statistically significant associations were observed between dementia worry and knowledge of dementia, self-perceived dementia risk, ageism, and dementia stigma in both samples. However, contrary to our expectations, the interaction effects for dementia worry level by country were insignificant.…”
Section: Discussionsupporting
confidence: 90%
“…Investigations of factors associated with dementia worry are also scarce. The most important and consistent factors described in the literature have included sociodemographic characteristics (increased age, female gender, and exposure to dementia), health characteristics (decreased general and cognitive health), psychological characteristics (increased depression and distress), and cognitive characteristics (increased dementia knowledge, and stigmatic beliefs) [ 3 , 4 , 5 , 6 , 7 ]. However, there may be other understudied factors associated with dementia worry, such as culture.…”
Section: Introductionmentioning
confidence: 99%